Oxidation, bromination, and methylenation of carbazole and (E)-3-(2-phenylethenyl)carbazole with HBr/DMSO; Chemistry of Heterocyclic Compounds; Vol. 28, iss. 11 - Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Filimonov V. D. Viktor Dmitrievich; Krasnokutskaya E. A . Elena Aleksandrovna; Kovaleva L. F. (1992, 1992)
Title screen